PENGARUH CSR DAN KINERJA LINGKUNGAN TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR SEKTOR BARANG KONSUMSI DI BEI 2021-2024 - Nafillah Rahmadiyanti; Lilis Lasmini; Dian Purwandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is directed toward examining the interrelation between CSR and environmental performance with the level of profitability in manufacturing entities within the consumer goods sector listed on the BEI during the 2021–2024 period. A quantitative approach is employed through both descriptive and verificative methods to yield a measurable empirical portrayal. Secondary data are utilized, derived from annual reports, sustainability reports, and PROPER reports as the primary informational foundation. The data processing procedure is conducted using the Partial Least Square (PLS) technique, assisted by the SmartPLS 4 software. The study reveals a negative and statistically significant influence of CSR on profitability, whereas environmental performance exhibits a positive yet non-significant association with profitability. This circumstance reflects that the enactment of CSR within a short-term horizon tends to exert a suppressive effect on the firm’s earnings generation, while the contribution of environmental performance has not yet been capable of delivering a substantial impetus toward profitability enhancement. In a comprehensive sense, CSR and environmental performance have not assumed a predominant role as principal determinants in shaping corporate profitability.